Application of nano silver / lecithin on wool through various methods :antibacterial properties and cell toxicity - Barani, Hossein (2020)
Silver nanoparticles (AgNPs) were synthesized with lecithin through a simple chemical reduction method. The prepared AgNPs/lecithin was then loaded into the wool fabric by exhaustion and pad-dry-cure methods. The surface morphology of the loaded wool fabrics was characterized by low-voltage scanning electron microscopy, and the loading efficiency was determined by inductively coupled plasma optical emission spectrometry. Further, the effect of the different lecithin concentrations was examined on the antibacterial activity, cytotoxicity, and color of the loaded wool fabrics. The loaded fabric with AgNPs at a higher lecithin ratio presented higher antibacterial activity due to the higher loading efficiency and smaller nanoparticle size. Also, the morphology of the fibroblast cells in cytotoxicity test was not changed in presence of extracted solution from the treated wool fabrics with different lecithin concentration.